The Twilight of Democracy in Post-Reformasi Indonesia: An Institutional Regression Analysis and the Resurgence of Authoritarian Patterns: Senjakala Demokrasi di Indonesia Pasca-Reformasi: Analisis Regresi Institusional dan Kebangkitan Pola Otoritarian - Arief Gunawan (Journal of State Democracy, 2025)
This study examines Indonesia’s democratic regression post-Reformasi through an interactive framework of three institutional pillars: security sector reform failure, party system dysfunction driven by cartelization and oligarchy, and the weakening of independent oversight bodies. Quantitative analysis of democracy scores (EIU, Freedom House, IDI) reveals stagnation and decline from 2014–2023, corresponding with controversial legislative revisions and judicial rulings eroding civil liberties. Literature review shows how political elites exploit unaccountable security apparatus to suppress opposition, while oligarchs finance parties to form fat coalitions that secure their interests. This political–security alliance systematically undermines the KPK and Constitutional Court via autocratic legalism, creating a vicious cycle of democratic regression. Findings confirm that regression is not isolated incidents but the product of destructive interactions among these pillars. The study concludes that structural reform of political funding, completion of security sector reform, and revitalization of civil society are essential for restoring democracy in Indonesia.